Collaborative roles in schoolwide bullying prevention: teachers’, psychologists’, and school principals’ shared responsibilities - Tulenbaevna, Myrzapeissova Meruyert; Atmaca, Taner; Tursynkyzy, Atemova Khalipa; Mamadaliyev, Sanzhar; Zholdasovna, Kuatova Zhyzira (Frontiers in Education, 2025)
This qualitative study explores the perceptions and experiences of teachers, school psychologists, and principals regarding bullying prevention among adolescent girls in schools in Shymkent, Kazakhstan. The research aims to understand the specific nature of bullying experienced by girls, assess the readiness of school staff to intervene, and identify the roles of key stakeholders in anti-bullying efforts. Data were collected through semi-structured interviews with 12 female and 2 male participants representing diverse roles in the school system. Thematic analysis revealed four key themes: (1) the relational and emotional nature of bullying among girls, (2) barriers to teacher intervention, including limited training and difficulty in recognizing covert behaviors, (3) collaborative efforts and multi-layered strategies for bullying prevention, and (4) the evolving gender dynamics in bullying patterns. While findings highlight promising practices such as anonymous surveys, role-playing activities, and partnerships with school psychologists, they also expose inconsistencies in school-wide policies and a need for standardized intervention protocols. The study underscores the importance of a whole-school approach and calls for targeted teacher training, structured coordination among staff, and policy-level reforms tailored to the cultural and systemic context of Kazakhstan.